PENGARUH PERMAINAN TRADISONAL TERHADAP KOMPETENSI INTERPERSONAL DENGAN TEMAN SEBAYA PADA SISWA SD (Studi Eksperimental pada Siswa Kelas 3 SDN Srondol Wetan 04-09 dan SDN Srondol Wetan 05-08 ) - Susanti, Fitria; Siswati, Siswati; Widodo, Prasetyo Budi (Jurnal Psikologi, 2010)
Child's world is a world of play. Through play, children can have greater opportunities to enhance social development, emotional development, and better able to develop interpersonal relationships because the child has the opportunity to interact with their peers. The pattern of play that involves interaction with colleagues can be found in traditional games. When playing traditional games, children are invited to gather and get to know their peers. This research was conducted to determine the effect of traditional game of interpersonal competence with peers in elementary school children.The population of this research is a third-grade students SDN Srondol Wetan 04-09 and SDN Srondol Wetan 05-08 with a sample size of 28 students. The sampling technique was using purposive sampling. Data collected by Interpersonal Competence Scale with Peer's (Î± = 0.805). The treatment given to the experimental group in the form of traditional games for six consecutive times with a duration of 75 minutes.Based on data analysis with statistical nonparametric methods Mann-Withney U test showed that there is interpersonal competence differences between children who participated in traditional games with children who do not follow traditional game activities. This is shown by the significant level of 0.924 (p>0.05) before treatment and the significance level of 0.000 (p> 0.05) after administration of treatment in the experimental group.Based on the analysis of research and is supported by previous studies, it can be concluded that the activities of Traditional Games influence of interpersonal competence with peers in elementary school children.Keywords : traditional games, interpersonal competence with peers, elementary school childrenPermalink :